Using Corticomuscular Coherence to Reflect Function Recovery of Paretic Upper Limb after Stroke: A Case Study - Zheng, Yang; Peng, Yu; Xu, Guanghua; Li, Long; Wang, Jue (Frontiers in Neurology, 2018)
Purpose: Motor deficits after stroke are supposed to arise from the reduced neural drive from the brain to muscles. This study aimed to demonstrate the feasibility of reflecting the motor function improvement after stroke with the measurement of corticomuscular coherence (CMC) in an individual subject. Method: A stroke patient was recruited to participate in an experiment before and after the function recovery of his paretic upper limb respectively. An elbow flexion task with a constant muscle contraction level was involved in the experiment. Electromyography (EMG) and electroencephalography (EEG) signals were recorded simultaneously to estimate the corticomuscular coherence. The non-parameter statistical analysis was used to test the significance of CMC differences between the first and second times of experiments. Result: The strongest corticomuscular coupling emerged at the motor cortex contralateral to the contracting muscles for both the affected and unaffected limbs. The strength of the corticomuscular coupling between activities from the paretic limb muscles and the contralateral motor cortex for the second time of experiment increased significantly compared with that for the first time. However, the corticomuscular coherence of the unaffected limb had no significant changes between two times of experiments. Conclusion: The results demonstrated that the increased corticomuscular coupling strength resulted from the motor function restoration of the paretic limb. The measure of corticomuscular coherence can reflect the recovery of motor function after stroke by quantifying interactions between activities from the motor cortex and controlled muscles.